2015
DOI: 10.1080/02640414.2014.1003583
|View full text |Cite
|
Sign up to set email alerts
|

Leg soft tissue position and velocity data from skin markers can be obtained with good to acceptable reliability following heel impacts

Abstract: Quantifying soft tissue motion following impact is important in human motion analysis as soft tissues attenuate potentially injurious forces resulting from activities such as running and jumping. This study determined the reliability of leg soft tissue position and velocity following heel impacts. A grid of black dots was applied to the skin of the right leg and foot (n = 20). Dots were automatically detected (ProAnalyst(®)) from high-speed records of pendulum and drop impacts. Three trained measurers selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…The marker design (2 x 2 cm grid of 0.5 cm diameter black dots) required no mechanical interaction with the leg, and was applied using flexible plastic stencils and a permanent black marker pen. Overall, Brydges et al (2015) reported good to acceptable reliability for this technique. Nonetheless, modifications to marker shape and contrast might help to further improve its capacity to automatically track soft tissue motion and reduce measurement error (Haddadi & Belhabib, 2008;Crammond, Boyd & Dulieu-Barton, 2013), especially across different skin pigmentations.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…The marker design (2 x 2 cm grid of 0.5 cm diameter black dots) required no mechanical interaction with the leg, and was applied using flexible plastic stencils and a permanent black marker pen. Overall, Brydges et al (2015) reported good to acceptable reliability for this technique. Nonetheless, modifications to marker shape and contrast might help to further improve its capacity to automatically track soft tissue motion and reduce measurement error (Haddadi & Belhabib, 2008;Crammond, Boyd & Dulieu-Barton, 2013), especially across different skin pigmentations.…”
Section: Introductionmentioning
confidence: 84%
“…Schematic diagram of the SLU marker design (2 x 2 cm square grid of 0.5 cm diameter circular black dots) on the forearm from (a) posterior and (b) lateral views; schematic diagram of the SNU marker design (2 x 2 cm square grid of ~1 cm diameter circular white dots with ~0.5 cm diameter random black dots overlaid on top) on the forearm demonstrating the contrast for (c) light and (d) dark skin pigmentations. a calibration unit of 6 cm was applied between four adjacent markers (in the same row) that were directly distal to the elbow (Stefanczyk et al, 2013;Brydges et al, 2015); the planar (2D) axes of the coordinate system were aligned in two directions (x-axis: parallel with the long axis of the radius and ulna, running in the proximal-distal direction; y-axis: perpendicular to the long axis of the radius and ulna, running in the anterior-posterior direction of the forearm) ( Figure 4). A single image filter (Convolve: Sharpening (3 x 3 Center)) was applied using the default settings to slightly enhance the overall sharpness of the raw video footage for better contrast and marker edge detection.…”
Section: Video Analysismentioning
confidence: 99%
See 3 more Smart Citations